PENGHIJAUAN SEBUAH IKHTIAR DALAM PELESTARIAN LINGKUNGAN DI KAMPUNG KLAFDALIM DISTRIK MOI SEGEN KABUPATEN SORONG - Azis Maruapey; Lona Helti Nanlohy; Fajrianto Saeni; Rajab Lestaluhu (Yayasan Education and Social Center, 2022)
Reforestation is one of the planting activities on vacant land with the aim that the land can be restored, maintained, and its fertility improved. Problems related to reforestation are how to make people aware of the benefits of reforestation for the environment and the importance of reforestation as an effort to preserve the environment. The purpose of the service with the topic of Greening an Effort in Environmental Preservation is to increase public awareness of the importance of reforesting the environment in order to reforest critical land by planting a number of trees that are suitable for local conditions. The service method is carried out using socialization by delivering material in classical form about the benefits and importance of reforesting the environment followed by tree planting in Klafdalin Village. The results of the socialization are expected to : a). Relevance: it is hoped that a sense of love for the environment will be fostered in order to maintain a green area in Klafdalin Village, Moi Segen District, Sorong Regency; b) Acceptability: this activity can be accepted by the people of Klafdalin Village, Moi Segen District, Sorong Regency and is supported by the local government and the community; c) Effectiveness: the process of delivering extension materials is carried out in simple language, located in a green area, and immediately ends with the planting of hundreds of tree seedlings by the community participating in the extension, namely Trembesi, Sengon, Kihujan, Linggua, Mahogany, Matoa, Tanjung, Rambutan and Durian trees; and d) Accuracy: the materials and socialization activities are very precise, making the people of Klafdalin Village, Moi Segen District, Sorong Regency more aware of how to take real action with an effort to conserve the environment by directly participating in planting trees in their surroundings